Overview of Phase-Change Electrical Probe Memory - Wang, Lei (Nanomaterials (Basel), 2018)
Phase-change electrical probe memory has recently attained considerable attention owing to its profound potential for next-generation mass and archival storage devices. To encourage more talented researchers to enter this field and thereby advance this technology, this paper first introduces approaches to induce the phase transformation of chalcogenide alloy by probe tip, considered as the root of phase-change electrical probe memory. Subsequently the design rule of an optimized architecture of phase-change electrical probe memory is proposed based on a previously developed electrothermal and phase kinetic model, followed by a summary of the state-of-the-art phase-change electrical probe memory and an outlook for its future prospects.